Numerical Ability in Problem Solving Among MTs NU Miftahul Huda: A Review of Cognitive Styles that Dependent and Independent of the Field of Study - Rachmatika, Fajriyah; mukhsinin, Hidayatul; Abir, Anisa (Delta-Phi: Jurnal Pendidikan Matematika, 2025)
Numerical skills and problem-solving are crucial competencies influenced by students' cognitive styles. This qualitative descriptive study aims to describe the numerical abilities of eighth-grade students of MTS NU Miftahul Huda Prigen in solving problems of the System of Linear Equations in Two Variables reviewed from the cognitive styles of Field Dependent (FD) and Field Independent (FI). Numerical abilities are measured through indicators of counting, logical thinking, organizing information, and identifying patterns, while the problem-solving process is guided by Polya's steps (understanding, planning, implementing, and re-checking). The research subjects were determined using the Group Embedded Figures Test (GEFT). Data were collected through numerical ability test instruments and interviews, then analyzed descriptively. The results of the study show significant differences between the two types of cognitive styles. Students with the FI cognitive style tend to be more independent, analytical, and organized in processing numerical data and are able to separate relevant information from the problem context. In contrast, FD students tend to need additional guidance, have difficulty in separating important information from complex contexts, and rely heavily on previously given example problems. This conclusion highlights the importance of an adaptive teaching approach to students' thinking characteristics in mathematics learning.